Kajian Jenis dan Makna Mantra Bertarung di Desa Tebat Laut Kecamatan Seberang Musi Kabupaten Kepahiang - Mardiansyah, Dodi; Zasrianita, Fera; Wediasti, Welti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT This study aims to describe the types and meanings of battle incantations in Tebat Laut Village, Seberang Musi District, Kepahiang Regency. The research method used is qualitative descriptive with a semantic approach. Data collection techniques include observation, interviews, and documentation. The data analysis process involves three stages: data reduction, data presentation, and conclusion drawing. The results show that the battle incantations in Tebat Laut Village serve to defeat enemies by combining spiritual power and natural symbolism. The incantations that paralyze the enemy emphasize the user's identification with divine power and nature, while the incantations that subdue the enemy create fear through symbols of strength, such as tigers. These two types of incantations not only function in physical conflicts but also strengthen social status, bravery, and cultural identity, affirming belief in spiritual power and existing social norms. In conclusion, there are two types of incantations: those that paralyze the enemy and those that subdue the enemy. Both incantations not only serve as verbal expressions in the context of battle but also as representations of the cultural values and fighting strategies of the people of Tebat Laut Village, reflecting hopes for victory and dominance in the conflicts they face. Keywords: Types, Meaning, Battle Incantations